1965
DOI: 10.1002/jhet.5570020209
|View full text |Cite
|
Sign up to set email alerts
|

Difluorodiazirine. V. difluoromethyl esters and ethers

Abstract: The preparation of difluoromethyl esters and ethers by the photolytic reaction of difluorodiazirine with acids and alcohols, respectively, is described. Difluoromethyl benzoate is converted, under mild conditions, to methyl benzoate, benzamide and benzanilide by reaction with methanol, ammonium hydroxide and aniline, respectively. The difluoromethyl esters are activated to nucleophilic reaction by virtue of the a-fluorine substitution . S d, J = 68.2 c/s t, J = 68.8 C/S t, J = 8.8 C/S 9, J = 8.8 c/s d, J = 68.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…[10,11] However, current syntheses of difluoromethyl ethers with :CF 2 reagents mainly focus on the difluoromethylation of phenols under basic conditions; [10] the difluoromethylation of alcohols under similar reaction conditions is usually less productive as aresult of the competitive reactions caused by the base.T od ate,o nly several reagents,i ncluding HCF 2 Cl, [12] BrCF 2 P(O)(OEt) 2 , [13] and TMSCF 2 Br, [14] have been reported for difluoromethylation of alcohols under basic conditions with limited functional group compatibility (Scheme 1a,b asic). Although some methods that can avoid strongly basic conditions by the use of special :CF 2 reagents, such as CF 2 N 2 , [15] HFPO, [16] and CF 3 ZnBr·2 CH 3 CN, [17] have been exploited for alcohol difluoromethylation, these methods usually require excess amounts of alcohols and suffer from narrow substrate scope (Scheme 1a,neutral). Recently, am odification of Chensm ethod has led to an effective difluoromethylation of primary and secondary alcohols with FSO 2 CF 2 CO 2 H(Scheme 1a,acidic); [18] however,the reaction with tertiary alcohols is still unmet.…”
mentioning
confidence: 99%
“…[10,11] However, current syntheses of difluoromethyl ethers with :CF 2 reagents mainly focus on the difluoromethylation of phenols under basic conditions; [10] the difluoromethylation of alcohols under similar reaction conditions is usually less productive as aresult of the competitive reactions caused by the base.T od ate,o nly several reagents,i ncluding HCF 2 Cl, [12] BrCF 2 P(O)(OEt) 2 , [13] and TMSCF 2 Br, [14] have been reported for difluoromethylation of alcohols under basic conditions with limited functional group compatibility (Scheme 1a,b asic). Although some methods that can avoid strongly basic conditions by the use of special :CF 2 reagents, such as CF 2 N 2 , [15] HFPO, [16] and CF 3 ZnBr·2 CH 3 CN, [17] have been exploited for alcohol difluoromethylation, these methods usually require excess amounts of alcohols and suffer from narrow substrate scope (Scheme 1a,neutral). Recently, am odification of Chensm ethod has led to an effective difluoromethylation of primary and secondary alcohols with FSO 2 CF 2 CO 2 H(Scheme 1a,acidic); [18] however,the reaction with tertiary alcohols is still unmet.…”
mentioning
confidence: 99%
“…To date, only several reagents, including HCF 2 Cl, BrCF 2 P(O)(OEt) 2 , and TMSCF 2 Br, have been reported for difluoromethylation of alcohols under basic conditions with limited functional group compatibility (Scheme a, basic). Although some methods that can avoid strongly basic conditions by the use of special :CF 2 reagents, such as CF 2 N 2 , HFPO, and CF 3 ZnBr⋅2 CH 3 CN, have been exploited for alcohol difluoromethylation, these methods usually require excess amounts of alcohols and suffer from narrow substrate scope (Scheme a, neutral). Recently, a modification of Chen's method has led to an effective difluoromethylation of primary and secondary alcohols with FSO 2 CF 2 CO 2 H (Scheme a, acidic); however, the reaction with tertiary alcohols is still unmet.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of early reports which operate under neutral conditions, have proven more effective. As early as 1965, Mitsch and Robertson 179 showed that the photolysis of difluorodiazirine could generate difluorocarbene and permit the difluoromethylation of a limited selection of alcohols. In 1995, Miethchen and co-workers reported the O-difluoromethylation of monosaccharides mediated by trifluoromethylzinc bromide, 180 and in 2005, Mizukado and co-workers described the use of hexafluoropropene oxide as a difluorocarbene reagent capable of reacting with aliphatic alcohols.…”
Section: (O/s/n)-difluoromethylationmentioning
confidence: 99%